Necroptosis and Neuroinflammation in Retinal Degeneration - Tao, Yan; Murakami, Yusuke; Vavvas, Demetrios G.; Sonoda, Koh-Hei (Frontiers in Neuroscience, 2022)
Necroptosis mediates the chronic inflammatory phenotype in neurodegeneration. Receptor interacting protein kinase (RIPK) plays a pivotal role in the induction of necroptosis in various cell types, including microglia, and it is implicated in diverse neurodegenerative diseases in the central nervous system and the retina. Targeting RIPK has been proven beneficial for alleviating both neuroinflammation and degeneration in basic/preclinical studies. In this review, we discuss the role of necroptosis in retinal degeneration, including (1) the molecular pathways involving RIPK, (2)RIPK-dependent microglial activation and necroptosis, and (3) the interactions between necroptosis and retinal neuroinflammation/degeneration. This review will contribute to a renewed focus on neuroinflammation induced by necroptosis and to the development of anti-RIPK drugs against retinal degeneration.